Neonatal presentation of Joubert syndrome - Choudhary, Rahul; Sachdeva, Garima; Katoch, Gaurav; Choudhary, Sanjeev (International Journal of Contemporary Pediatrics, 2020)
Joubert syndrome is a rare genetic disorder with autosomal recessive or rarely X-linked recessive inheritance. Authors are reporting a case of a newborn girl with Joubert syndrome who presented with respiratory distress, hypotonia, hyporeflexia, abnormal eye movements, and facial dysmorphism. Brain MRI revealed vermian hypoplasia, “molar tooth sign” with “bat wing appearance” of the fourth ventricle, deepened interpeduncular fossa, and elongated superior cerebellar peduncles. The clinical diagnosis of this syndrome is difficult due to its variable presentation and non-specific presentation. Magnetic Resonance Imaging (MRI) has an important role in the diagnosis of Joubert syndrome. This not only helps in early diagnosis but also helps in appropriate counseling and proper rehabilitation of the baby.